Estimation of Serum CD200 and CD200R1 Levels in a Sample of Iraqi Women with Breast Cancer: Their Role as Diagnostic and Prognostic Markers - Ismail, Adnan M.; Saleh, Eman S (Iraqi Journal of Pharmaceutical Sciences, 2020)
Breast cancer is a disease in which cells in the breast grow out of control. CD200 is a cell surface glycoprotein expressed on many cells, it belongs to the immunoglobulin family (Ig) and have a great role in the regulation of inflammation in autoimmunity. CD200 is the ligand for CD200R1 receptor. To determine if serum level of CD200 and its receptor CD200R1 can be used as a diagnostic and prognostic marker in patients with breast cancer.This case control study was carried out at Oncology Teaching Hospital – Medical city in Baghdad. Six groups were enrolled, four groups were confirmed with breast cancer stage (I, II, III and IV), fifth group (benign) and sixth group was control (healthy individual). Serum is divided to measure CD200 and CD200R1 by utilizing quantitative sandwich enzyme-linked immunosorbent assay (ELISA) Kits.Serum level of CD200 was significantly different (P=0.000088) between breast cancer patients and control only, serum level of CD200 increases with disease stage and there is a significant positive correlation. Serum level of CD200R1 was different with stage, although the differences were not significant but the level of CD200R1 is lower in stage 4 patients than other stages.Serum CD200 level can be used as a diagnostic marker for breast cancer. Serum level of CD200R1 can be used as a prognostic marker